Investigation of injection through bending magnet fringe fields in X-rays source based on the H-100M storage ring - Gladkikh, P.I.; Mytsykov, A.O.; Rezaev, A.V.; Zelinsky, A.Yu. (Вопросы атомной науки и техники, 2004)
In paper the injection in the X-ray source based on the H100-M storage ring, through fringe fields of a bending magnet
is considered. The simulation of charged particle beam motion through 3-d fields of magnetic devices of the injection
channel located on the ring, is performed. The focusing properties of the injection channel are determined. Розглядається інжекція в джерело рентгенівського випромінювання на основі нагромаджувача Н-100М через розсіяні поля поворотних магнітів. Проведено моделювання руху пучка заряджених часток через трьохмірні поля
магнітних елементів каналу інжекції. Визначені фокусуючи властивості каналу інжекції. Рассматривается инжекция в источник рентгеновского излучения на основе накопителя Н-100М через рассеянные
поля поворотных магнитов. Проведено моделирование движения пучка заряженных частиц через трехмерные поля магнитных элементов канала инжекции. Определены фокусирующие свойства канала инжекции.